Bayesian analysis of weak gravitational lensing and Sunyaev-Zel'dovich data for six galaxy clusters - Hurley-Walker, N; Bridle, S; Cypriano, E; Davies, M; Erben, T; Feroz, F; Franzen, T; Grainge, K; Hobson, M; Lasenby, A; Marshall, P; Olamaie, M; et al. (2012)
We present an analysis of observations made with the Arcminute Microkelvin Imager (AMI) and the Canada-France-Hawaii Telescope (CFHT) of six galaxy clusters in a redshift range of 0.16-0.41. The cluster gas is modelled using the Sunyaev-Zel'dovich (SZ) data provided by AMI, while the total mass is modelled using the lensing data from the CFHT. In this paper, we (i) find very good agreement between SZ measurements (assuming large-scale virialization and a gas-fraction prior) and lensing measurements of the total cluster masses out to r 200; (ii) perform the first multiple-component weak-lensing analysis of A115; (iii) confirm the unusual separation between the gas and mass components in A1914 and (iv) jointly analyse the SZ and lensing data for the relaxed cluster A611, confirming our use of a simulation-derived mass-temperature relation for parametrizing measurements of the SZ effect. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.